The effect of physical exercise intervention on the ability of daily living in patients with Alzheimer’s dementia: a meta-analysis - Liu, Chenyu; Gao, Shiying; Li, Shanshan (Frontiers in Aging Neuroscience, 2024)
Objective To systematically evaluate the effect of physical exercise intervention on the activities of daily living (ADL) on patients with Alzheimer’s dementia (AD) and explore the optimal exercise scheme. Methods PubMed, EMBASE, the Cochrane Library, Web of Science, and Science Direct databases were searched from 1987 to December 2023 to collect randomized controlled trials (RCTs). Two investigators independently screened the literature and extracted data according to the inclusion and exclusion criteria. The quality of the included studies was evaluated using Cochrane Review Manager 5.3. And STATA 16.0 was used for performing the meta-analysis. Results Fifteen randomized controlled trials were included. The results of the meta-analysis showed that physical exercise had a positive effect on the improvement of ADL in patients with AD [standardized mean difference (SMD) = 0.312, 95% confidence interval (CI 0.039–0.585), P = 0.02], and the difference was statistically significant. The results of subgroup analysis showed that anaerobic exercises such as strength and balance training with a medium cycle of 12–16 weeks and lasting 30–45 min each time were more ideal for the improvement of basic daily living ability of AD patients. Conclusion Physical exercise can effectively improve activities of daily living in patients with Alzheimer’s dementia and it may be a potential non-drug treatment for AD patients.